PENGARUH TINGKAT PENDIDIKAN, KUALITAS PELATIHAN, PENGALAMAN KERJA APARATUR DESA DAN FASILITAS KANTOR TERHADAP PEMAHAMAN LAPORAN KEUANGAN (Studi Empiris Pada Desa-Desa Sekecamatan Boawae Kabupaten Nagekeo) - Tato, Nofriani; Sayang, Sabulon; Kapa, Sesilianus (Jurnal Riset Ilmu Akuntansi, 2022)
The formulation of the problem in this study is: 1. Does the level of education affect the understanding of village financial reports in the Boawae sub-district, Nagekeo district?, 2. Does the quality of training affect the understanding of village financial reports in the Boawae sub-district, Nagekeo district?, 3. What is the work experience of village officials? effect on the understanding of village financial reports in Boawae sub-district, Nagekeo district?. 4. Do village office facilities affect the understanding of village financial reports in the Boawae sub-district, Nagekeo Regency?. This type of research used by the author is quantitative with a survey method. The sampling technique in this study used purposive sampling. With the number of respondents as many as 42 people. Based on test results. 1. The level of education influences the understanding of financial reports with tcount > ttable (2.767 > 2.026). 2. Training has an effect on understanding financial reports with tcount > ttable (2.652 > 2.026). 3. Work experience influences the understanding of financial reports with tcount > ttable (3.023 > 2.026). 4. Office facilities affect the understanding of financial reports with tcount > ttable (2.923 > 2.026).